2021
DOI: 10.3390/pathogens10050554
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Babesia bovis-Free Tick Colony Following Treatment of the Host with Diminazene Aceturate (Berenil)

Abstract: Babesia bovis is a widely-spread tick-borne hemoparasite of cattle with major economic and animal welfare consequences. Rhipicephalus (Boophilus) annulatus is a one-host tick which transmits bovine babesiosis in the Middle East and Africa. Laboratory rearing of ixodid ticks is essential for the investigation on ticks or tick-borne diseases. Establishing a tick colony in the laboratory usually originates from ticks harvested in the field, which may be naturally infected with various pathogens. This especially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Hyalomma lusitanicum is an important vector of Crimean-Congo haemorrhagic fever virus (CCHFV) in Iberia (Negredo et al, 2017;Cuadrado-Matías et al, 2022). Rhipicephalus annulatus transmits Babesia bigemina, B. bovis, and Anaplasma marginale, among others, to livestock (Tirosh-Levy et al, 2021). Meanwhile, I. ricinus is the major vector of the different Borrelia burgdorferi genospecies and of flaviviruses within the tick-borne encephalitis virus complex (Gern and Humair, 2002;Mansfield et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hyalomma lusitanicum is an important vector of Crimean-Congo haemorrhagic fever virus (CCHFV) in Iberia (Negredo et al, 2017;Cuadrado-Matías et al, 2022). Rhipicephalus annulatus transmits Babesia bigemina, B. bovis, and Anaplasma marginale, among others, to livestock (Tirosh-Levy et al, 2021). Meanwhile, I. ricinus is the major vector of the different Borrelia burgdorferi genospecies and of flaviviruses within the tick-borne encephalitis virus complex (Gern and Humair, 2002;Mansfield et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the standard therapies for babesiosis were diminazene aceturate (DA) and imidocarb dipropionate [ 8 , 9 ]. However, they have significant drawbacks, such as a long time to remove tissue, toxicity, and, in the case of DA, unavailability in certain regions [ 9 ]. Furthermore, new research has revealed that Babesia parasites may develop DA resistance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%